An “I” Locked in a Barrel “Would Not Know How to Speak”: Field of Experience, Dialogue, and Encroachment in Merleau-Ponty - Marina De Palo (Histoire Épistémologie Langage, 2023)
This article will illustrate the development of the theme of language within Maurice Merleau-Ponty’s The Prose of the World (1973) in relation to Saussurean linguistics and Hendrik Pos’s phenomenology of language. Focusing on the concept of encroachment (empiètement) and on the inter-penetration between one’s own body and the other’s body, it will illustrate the strategic role played by an open conception of the field of experience and of history’s dynamic sedimentation.